Tourist Perception and Interest in Visiting the Tanjung Benoa Tourism Area Amid Climate Change in 2025 - Amalia, Firdausha; Wijaya, Hananda Surya; Ningrum, Mega Ratna; Gusti, Putri Pinaring; Rhomadhani, Noviana Ardi; Habibilah, Burhanuddin; Nurhidayat, Muhammad Zaky; Wijaya, Arya Tri; Nurfauzi, Ivant Aditya; Prasetyo, Dwi; Alhakim, Fakhri Taufik; Priyana, Yuli (Universitas Muhammadiyah Surakarta, 2024)
Climate change refers to long-term changes in global or regional weather patterns, which can involve changes in temperature, rainfall, wind speed, and other weather phenomena. This research aims first to analyze tourists' perceptions of climate change and its impact on the tourist attraction of Tanjung Benoa, second to determine the influence of climate change on tourists' interest in visiting Tanjung Benoa, third to identify factors that influence tourists' decisions in choosing tourist destinations amidst the issue of climate change. Using qualitative methods, data was collected through a survey of 50 domestic tourist respondents. The research results show that most tourists are aware of the impact of climate change on the ecosystem and natural beauty of Tanjung Benoa, although there are still those who do not understand this issue. Tourist interest in visiting again is quite high, especially in the 25-29 year age group. However, climate change such as coastal erosion, rising sea levels and damage to coral reefs could threaten the region's tourist attraction. It is hoped that this research can become the basis for developing resilient and environmentally friendly tourism in Tanjung Benoa.